Women and gender stereotyping in media from the point of view of structuration theory - Awanis Akalili; Indah Olivia Sari (Journal of Social Studies (JSS), 2021)
This research is a thought process on social structure that is not understood as the consequence of human repetitive action. This has become folkways, causing gender stereotyping of women even more perpetuated by media's various narrations. This research aims to describe gender stereotyping of women in Indonesian television media. This was done by analyzing the broadcasting shows by using Gidden's theory of structuration. This descriptive research is a literary study that includes books, journals, researches and websites as the data. The collected data then analyzed by using Giddens' structuration theory. This article began with the review on structuration theory. Next is a review on structuration theory from the point of view of commmunication study. The gender stereotyping of women case in the media was then broken down and analyzed by using structuration theory. The result showed that the agent's action and the structure are inseparable, in harmony with Gidden's concept of duality. In fact, many women have put up a fight against this gender stereotyping through social-feminist movements. On the other hand, they actually do follow the existing structure both unconsciously and consciously. This structure, however, is still growing among the people of modern society.